PERANAN NOMOR POKOK PENGUSAHA BARANG KENA CUKAI TERHADAP PENDAPATAN CUKAI INDUSTRI MINUMAN MENGANDUNG ETIL ALKOHOL DI BALI - Deya Pramana, I Gede; Parsa, I Wayan; Suardita, I Ketut (Kertha Wicara : Journal Ilmu Hukum; Vol.2, No.1 Edisi Februari 2013, 2013)
Alcoholic beverages is subject of ecise tax permits are required for alcoholic beverages factorycirculation of alcoholic beverages in bali very rapidly due to support in the tourism sector so thatthe necessary supervision both potential tax revenue through the provision of permit as well as aviolation that may be performed by the manufacturer alkoholic beverages. This research uses fieldresearch, quantitative descriptive approach using Spearman Rho. The results showed a positivecorrelation to the acquisition of the ownership permit customs and undiscovered violations ofownership permit of alcoholic beverages manufacturers in Bali from 2008 to 2012 (april).
Keywords: taxtation excise alcohol beverage